The validation of a screening tool for the identification of feeding and swallowing difficulties in the paediatric population aged 0-2 years admitted to general medical wards - Sibanda, Cynthia (Department of Health and Rehabilitation Sciences, 2020)
Background: Feeding and swallowing difficulties (FSD) have been found in typically developing children as well as in children with complex medical conditions and developmental disabilities. These difficulties cause negative health consequences such as aspiration pneumonia, chronic lung disease, failure to thrive, prolonged hospital stay and even death. The early identification and management of feeding and swallowing difficulties is important as it prevents the negative effects on health and quality of life. Hence, there is a need for a validated screening tool to use in the general hospitalized paediatric population. Research Aims: The aim of this study was to validate the Feeding and Swallowing Questionnaire as a screening tool, in the paediatric population aged 0 – 2 years admitted to general medical wards. The secondary aim was to describe the FSD presenting in the paediatric population aged 0 - 2 years who are hospitalized in the general medical wards. Methodology: A prospective, descriptive, clinimetric design was utilized. A sample of 107 participants admitted to the general medical wards at Steve Biko Academic Hospital were included in the study. Participants’ feeding and swallowing was screened by a research assistant using the Feeding and Swallowing Questionnaire. After the screening, a clinical feeding and swallowing assessment was conducted for comparison, the assessment was conducted by the student researcher using the Clinical Feeding and Swallowing Assessment Tool. Results: There was a 27% FSD prevalence, with the majority of cases (92%) occurring in children under one year of age. One hundred and three children (63% male; median (IQR) age 5.2 (2.1 – 12.8) months) underwent screening and clinical assessment for feeding and swallowing disorders. The criterion validity of the Feeding and swallowing Questionnaire was established with a sensitivity of 88% and a specificity of 32%. Internal consistency was achieved with an acceptable Cronbach’s alpha of 0.79, and good inter-rater reliability (80%). Participants presented with feeding difficulties in all the phases of swallowing, while some participants had behavioural feeding difficulties. Those who had FSD had the following medical conditions: cardiorespiratory, neurological and gastrointestinal disorders namely acute gastroenteritis and liver disease. Feeding and swallowing difficulties were associated with increased mealtime duration (p=0.005) and supplementary oxygen support (p=0.03). Conclusion: The results confirm that the Feeding and Swallowing Questionnaire shows promising findings as a reliable and valid tool for the identification of FSD in the general hospitalized paediatric population. However, further research in other setting with general paediatric medical wards is required to increase the robustness of the screening tool.